P071 Supporting extrapolation of indications for ABP 501, the first adalimumab biosimilar: focus on Crohn's disease. (25th January 2019) - Halder, S; Khan, W; Wang, X; Kuhns, S; Sweet, H; Reinisch, W; McBride, H
Abstract: Background: ABP 501 (EU: AMGEVITA® [adalimumab]; US: AMJEVITA™ [adalimumab-atto]) is the first approved biosimilar to adalimumab (HUMIRA®). The primary mechanism of action (MOA) of adalimumab is mediated by binding to soluble tumour necrosis factor (TNF)-α, inhibiting its proinflammatory signalling. Secondary mechanisms mediated by binding to membrane bound (mb) TNF-α may play a role in inflammatory bowel disease (IBD) and include reverse signalling, mixed lymphocyte reactions (MLRs) and effector functions such as antibody-dependent cell-mediated cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC). To support extrapolation to IBD, specific ex vivo functional studies explored the similarity of ABP 501 to adalimumab reference product (RP) in these mechanisms. Methods: Multiple lots of ABP 501 and RP sourced from the USA (US) and the European Union (EU) were compared. Binding of ABP 501 and RP to soluble TNF (sTNF) α and mbTNF α were tested. Blocking of TNF α-induced caspase activation, IL-8 secretion and lymphotoxin (LT)-α (TNF-β) bioactivity (ie, specificity) were also assessed. To confirm similarity in Fc-mediated functions, ADCC using engineered NK92 cells expressing the high-affinity variant of FcgRIIIa (158V) and CDC were tested. ADCC was also assessed in peripheral blood mononuclear cells (PBMCs) isolated from healthy volunteers and patients with Crohn's disease. Results: Relative binding to sTNF α was similar [ABP 501, 108%; RP (EU), 111%; RP (US), 112%], demonstrating similarity in potency. Relative binding to mbTNF α was also similar [ABP 501, 103%; RP (EU), 106%; RP (US), 105%]. Relative activity in reverse signalling was similar [ABP 501, 99%; RP (EU), 99%; RP (US), 98%]. Relative activity was similar in NK92 ADCC [ABP 501, 85%; RP (EU), 87%; RP (US), 86%] and CDC [ABP 501, 100%; RP (EU), 94%; RP (US), 94%]. PBMCs isolated from healthy volunteers and patients with Crohn's disease showed similar, dose-dependent ADCC activity with all three agents. Conclusions: ABP 501 adalimumab biosimilar has previously been shown to be highly similar to adalimumab RP in several analytical assessments, clinical pharmacokinetics, efficacy, safety and immunogenicity. We have demonstrated that similarity extends to biological activity across key MOAs, including those mediated through mbTNF-α that may be important for the efficacy of adalimumab in IBD. Coupled with previously reported effector function and reverse signalling assessments, ex vivo ADCC activity in PBMCs isolated from healthy volunteers and patients with Crohn's disease contribute to the totality of evidence supporting efficacy of ABP 501 in IBD.